Russian extreme hypertriglyceridemia registy (REGGI): a call to action - U. V. Chubykina; M. V. Ezhov; A. A. Sokolov; P. A. Vasiluev; O. N. Ivanova; E. Y. Zakharova (Рациональная фармакотерапия в кардиологии, 2024)
Hypertriglyceridemia (HTG) is associated with an increased risk of atherosclerotic cardiovascular disease, pancreatitis developing, and all-cause mortality. The risk escalates with rising triglyceride levels and is most significant in extreme HTG (triglycerides above 10 mmol/L). According to epidemiological studies in the Russian Federation, the extreme HTG prevalence varies between 0.1-0.2% (affecting 146,000 to 292,000 Russians). Extreme HTG can be monogenic or polygenic (multifactorial), this determines the clinical course of the disease. Registries are among the most effective models for studying disease development, as they can compile information on clinical, laboratory, instrumental, and molecular data from patients with specific pathologies, and enable analysis of this data and the subsequent development and integration of improved diagnostic and treatment models into clinical practice. The establishment of a registry for extreme HTG will deepen our understanding of the hyperlipidemia nature, regional characteristics of its prevalence, and the phenotypic manifestation of the disease in our country. It will also facilitate the organized and standardized collection of patient information. Data obtained through registry monitoring will enhance diagnostic and monitoring approaches for patients with extreme HTG in practical healthcare settings. The purpose is to present current information on the diagnosis, monitoring, and treatment of patients with extreme HTG, and to announce the creation of the Russian Extreme hypertriGlyceridemia reGIstry (REGGI).